Direct Bilateral Free Trade Agreement (BFTA) to ASEAN's Intra-Regional Trade & lndividual Country's Investment Creation: The Case of Indonesia, Malaysia & Thailand 1988-2008 - Verico, Kiki (Economics and Finance in Indonesia, 2011)
.